2018
DOI: 10.1002/phar.2131
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Elimination in Four Patients With a CYP3A5*3/*3 CYP3A4*22/*22 Genotype Combination

Abstract: Cytochrome P450 3A5 (CYP3A5) and cytochrome P450 3A4 (CYP3A4) are the predominate enzymes responsible for tacrolimus metabolism. The presence of CYP3A4 and CYP3A5 genetic variants significantly affects tacrolimus clearance and dose requirements. CYP3A5*3 is a loss-of-function variant resulting in no CYP3A5 enzyme production. CYP3A4*22 is a variant that reduces production of functional CYP3A4 protein. Caucasians commonly carry these variant alleles but are very rarely homozygous for both CYP3A5*3 and CYP3A4*22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
(33 reference statements)
0
16
1
Order By: Relevance
“…We evaluated the four variants (CYP3A5*3, *6, *7, and CYP3A4* 22) known to be strongly associated with tacrolimus metabolism and the AF of CYP3A5*3 was 0.92 which is slightly higher than what we observed (0.84). They also found that CYP3A5*6 and *7 were not present.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…We evaluated the four variants (CYP3A5*3, *6, *7, and CYP3A4* 22) known to be strongly associated with tacrolimus metabolism and the AF of CYP3A5*3 was 0.92 which is slightly higher than what we observed (0.84). They also found that CYP3A5*6 and *7 were not present.…”
Section: Discussioncontrasting
confidence: 64%
“…13,14 The CYP3A5 variant, CY3A5*3 (rs776746), is a loss-of-function variant and has been well studied with tacrolimus pharmacokinetics. [18][19][20][21][22] We have shown in our work that up to 50% of variability in tacrolimus pharmacokinetic is explained by CYP3A genetic variants and clinical factors. 17 CYP3A4*22 (rs35599367) is also a reduced-function variant which occurs primarily in European ancestry and is associated with variation in tacrolimus pharmacokinetics.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…In the current study, sensitivity analyses demonstrated 30–50% decreases in hepatic CYP3A4 resulted in 1.6‐fold to 2.3‐fold increases in trough concentration in a virtual CYP3A5 PM, where intestinal CYP3A4 expression level was not changed. In fact, Scheibner et al . recently reported that the median dose‐normalized tacrolimus trough concentration in CYP3A5 *3/*3 and CYP3A4 *22/*22 (3.05 ng/mL/mg of total daily dose, n = 4) was 1.9‐fold higher compared with CYP3A5 *3/*3 and CYP3A4 *1/*1 (1.60 ng/mL/mg of total daily dose; n = 1,048) in the first 6 months post transplant.…”
Section: Discussionmentioning
confidence: 99%